Evaluation of the QuEChERS and magnetic micro dispersive solid-phase extraction of brominated flame retardants in red fruits with determination by GC/MS. (30th March 2020) - Cruz Fernandes, Virgínia; Freitas, Maria; Pacheco, João G.; Fernandes Domingues, Valentina; Delerue-Matos, Cristina
Highlights: Optimization of a QuEChERS extraction combined with MµdSPE for BFRs analysis. Analytical evaluation of GC/MS as a screening tool for BFRs detection in red fruits. MNPs were used as sorbents in the MµdSPE purification step. Application the new sample preparation methodology in the analysis of BFRs. Abstract: A sample preparation method, QuEChERS extraction combined with a magnetic micro dispersive solid phase extraction (MµdSPE), was optimized and evaluated for the trace analysis of 9 brominated flame retardants in red fruit samples (strawberries, blueberries, and raspberries) using gas chromatography-mass spectrometry. Magnetic nanomaterials were used as sorbents providing an extraction of the target compounds. Linearity was established for all the analytes (from 10 to 200 µg kg −1 ). Seven concentration levels were analyzed with three measurements at each concentration. Linear responses (R 2  > 0.99) were obtained, recoveries of all target analytes were within the range of 65–141%, relative standard deviations were <20% at all three spiking levels, while intraday and interday precisions were below 20%. This study demonstrated that the new sample preparation with magnetic nanoparticles could potentially be expanded to extract and pre-concentrate the BFRs in different red fruit samples. The method has been successfully applied to study BFRs in 12 samples from conventional and organic farming.